The Drugs and Clinical Trial Rules: An Overview - Vishal Vennu (India’s New Drugs and Clinical Trial Rules: Perception and Perspectives of Indian Researchers, 2021)
Globally, most nations follow the regulations to closely supervise clinical trials to evaluate their data integrity, protect patients’ safety, and assess sites and sponsors’ adequacy. The chapter provides an overview of these clinical trial regulations. The chapter also highlights the clinical trial regulations that began and developed to control medical therapies due to unethical human experiments. In addition, the chapter outlines India’s drug and clinical trial regulatory systems development over the past decades, the new changes, and it is important to know these changes by researchers.